Peran Public Relations Dalam Membangun Reputasi Perguruan Tinggi - Yera Yulista (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
The development of higher education institutions in Indonesia indicates the increasing meaning of education in the community so that the existence of educational institutions becomes the target for stakeholders, especially students / prospective students. In general, to maintain the existing stakeholders clearly requires the establishment of a good reputation in the community. One of the parties that can help higher education institutions in building the reputation of higher education is the presence of public relations. PR represents the institution in implementing the communication program to be a bridge between the organizations represented by the university stakeholders. Abstrak Perkembangan lembaga pendidikan tinggi di Indonesia menandakan semakin meningkatnya arti pendidikan di tengah masyarakat sehingga keberadaan lembaga pendidikan menjadi incaran bagi stakehoder khususnya mahasiswa/ calon mahasiswa. Secara umum untuk mempertahankan stakeholder yang ada jelas memerlukan pembentukan reputasi yang baik ditengah masyarakat.Salah satu pihak yang dapat membantu lembaga pendidikan tinggi dalam membangun reputasi perguruan tinggi adalah dengan kehadiran public relations. PR mewakili lembaga dalam melaksanakan program komunikasi untuk menjadi jembatan penghubung antara organisasi yang diwakili dengan stakeholder perguruan tinggi.